2013
DOI: 10.1021/ma302412v
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Poly(N-C3 glycine)s

Abstract: Ring-opening polymerization of N-substituted glycine Ncarboxyanhydrides (NCAs) was applied to prepare a series of welldefined poly(N-C3 glycine)s (C3 = n-propyl, allyl, propargyl, and isopropyl), polypeptoids, with molecular weights in the range of 1.8−6.6 kg mol −1 . Poly(N-isopropyl glycine), a previously unreported polypeptoid, could be obtained by bulk polymerization of the corresponding NCA in the melt. The samples were characterized by spectroscopy (NMR and FT-IR), size exclusion chromatography (SEC), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(157 citation statements)
references
References 36 publications
(67 reference statements)
8
139
1
2
Order By: Relevance
“…In particular, the successful preparation of a pentablock quinquiespolymer highlighted the unique character of the NNCA NuLROP [23]. Moreover, efficient polymer analogue modification [24,25] and thermo-responsiveness [26,27] of polypeptoids was described.…”
Section: Open Accessmentioning
confidence: 99%
“…In particular, the successful preparation of a pentablock quinquiespolymer highlighted the unique character of the NNCA NuLROP [23]. Moreover, efficient polymer analogue modification [24,25] and thermo-responsiveness [26,27] of polypeptoids was described.…”
Section: Open Accessmentioning
confidence: 99%
“…[15][16][17][18][19][20] The relative cell viability was found to be dependent on the polymer composition and concentration. It was found that relative cell viability decreases with increasing polymer concentration for all polymers (Figure 13).…”
Section: Cytotoxicitymentioning
confidence: 98%
“…In recent years, the substrate scope for polymerization studies was further expanded to include a variety of R-NCA monomers bearing various N-substituents ( Figure 2). [5,6,[15][16][17][18][19][20][21][22] Luxenhofer et al demonstrated that the polymerizations of Me-NCAs using benzyl amine initiators were shown to proceed in a controlled manner without chain transfer or termination events, producing polysarcosines with narrow Poisson distribution (PDI < 1.1-1.3) and M n s that can be controlled by the initial monomer to initiator feed ratios. [56] The molecular distribution remains narrow (PDI 5 1.01-1.07) even after ten sequential polymerizations of Me-NCA monomers (DP < 100), attesting to the robustness of the living polymerization and suggesting the potential uses of the methods towards the synthesis of well-defined block copolypeptoids via sequential monomer addition.…”
Section: Synthesis Of Linear Polypeptoidsmentioning
confidence: 99%
See 2 more Smart Citations